Sifat fisikokimia beras analog berbasis pati talas beneng dan pati jagung dengan substitusi agar dari rumput laut (Glacilaria sp.): Physicochemical properties of analog rice based on beneng taro starch and corn starch with agar substitution from seaweed (Glacilaria sp.) - Khodijah; Aditia, Rifki Prayoga; Haryati, Sakinah (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
Analog rice is an artificial rice product that resembles the shape and texture of conventional rice. This study aimed to determine the optimal concentration of agar flour (Gracilaria sp.) substitution in the formulation of analog rice based on beneng taro starch and corn starch. A Completely Randomized Design (CRD) was used with four levels of agar flour concentration: 0%, 5%, 7.5%, and 10%. The research stages included the production of analog rice, evaluation of physical characteristics (whiteness degree, rehydration capacity, and expansion ratio), chemical properties (moisture, ash, fat, protein, carbohydrate), and hedonic test (appearance, aroma, taste, and texture). Data were analyzed using SPSS version 20.0, and the best treatment was determined using De Garmo’s effectiveness index. Nutritional Adequacy Rate (RDA) values were calculated using Microsoft Excel. The results showed that the best treatment was 7.5% agar flour substitution. The physical characteristics included an expansion ratio of 110%, rehydration capacity of 107%, and whiteness degree of 31.2%. The chemical composition consisted of 11.30% moisture, 1.89% ash, 0.18% fat, 1.73% protein, 84.80% carbohydrates (by difference), and 5.40% dietary fiber. The hedonic test results showed scores for appearance (5.07), smell (5.53), taste (5.10), and texture (6.03). These results indicate that the substitution of Gracilaria sp. agar flour can improve the physical, chemical, and sensory characteristics of analog rice.